The International Oryza Map Alignment Project (IOMAP): the Americas—past achievements and future directions - Alsantely, Aseel (2022)
The wild relatives of rice hold unexplored genetic diversity that can be employed to feed an estimated population of 10 billion by 2050. The Oryza Map Alignment Project (OMAP) initiated in 2003 has provided comprehensive genomic resources for comparative, evolutionary, and functional characterization of the wild relatives of rice, facilitating the cloning of >600 rice genes, including those for grain width (GW5) and submergence tolerance (SUB1A). Following in the footsteps of the original project, the goal of ‘IOMAP: the Americas’ is to investigate the present and historic genetic diversity of wild Oryza species endemic to the Americas through the sequencing of herbaria and in situ specimens. The generation of a large diversity panel describing past and current genetic status and potential erosion of genetic variation in the populations will provide useful knowledge for the conservation of the biodiversity in these species. The wild relatives of rice in the Americas present a wide range of resistance traits useful for crop improvement and neodomestication approaches. In the race against time for a sustainable food future, the neodomestication of the first cereal species recently accomplished in O. alta opens the door to the potential neodomestication of the other wild Oryza species in Americas.